Impacto en los niveles de colinesterasa en agricultores de tomate (Solanum lycopersicum L) en la localidad de San Luis, Chimborazo por efecto del uso de insecticidas organofosforados y carbamatos - Lindao Córdova, Víctor Alberto (2017)
This research aimed to determine the application conditions that affect cholinesterase levels, and generate a neurotoxic risk by the use of carbamates and organophosphates to tomato farmers (Solanum lycopersicum L.) in the town of San Luis, Chimborazo - Ecuador. The technique used was spectrophotometry. Cholinesterase examination was carried out in patients exposed to organophosphate and carbamate insecticides. The method used was the kinetic spectrophotometric (405 nm at 37 °C). Through factor analysis, the Kruskal Wallis and correlations were determined, the variables that affect cholinesterase levels. For the neurotoxicological analysis, it was applied, the questionnaire Psychologisch Neurologischeò Fragebogen (PNF) to each of the farmers, which allowed us to determine the presence of, clinical disorders, behavioral and neurological, in workers exposed to organophosphate and carbamate pesticides. Concluding that the variables that affect cholinesterase levels are: humidity, temperature in the greenhouse, time when grown tomato, state of application equipment, while remaining in the greenhouse, frequency of application of insecticides, read the label, time of insecticides application, and the most affected areas were psycho neurovegetative instability (PN), irritability (E), deficiency of concentration and memory (K) and asthenia (a).